Gig economy changing labor relations in the state of welfare in Finland - Komulainen, Katariina (Riga Graduate School of Law, 2022)
The gig economy has been shifting the labor markets to a new and unexplored pathway. Recently, the technological developments and globalization there has been a new conceptual understanding of work that begs to differ from the 20th century industrial setting. The commonly used term, future of work, refers to the fact that the way of working has been transforming to challenge the existing social construes. The research aims to focus on the labor relation transformation in the context of a welfare state. The welfare states are founded on strong sense of safety net gained through strong labor relations. Hence, the relationship between the change of labor relations and future of welfare state are strongly linked to each other. The future of work mainly challenges the classification of the labor that is the root for the entire regime of labor laws. Currently, welfare states are doomed because of their inflexibility to respond the changing nature of labor status.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Labour law; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Social welfare law; The Republic of Finland; Gig economy